Reconsidering Zeest’s “Samian” and “Protothasian” archaic lineages of transport amphoras - Dupont, P. (Materiale și Cercetări Arheologice)
The duality of Zeest’s geographical attribution of her “Samian” and “Protothasian” archaic lineages of transport amphoras both to East‑Greek and North‑Aegean centres of manufacture is reassessed in the light of lab results